Genomic analysis reveals population structure and selection signatures in plateau dairy cattle - Shangzhen Huang; Longgang Ma; Bin Li; Jinhuan Dou; Qing Xu; Yachun Wang (BMC Genomics)
Abstract Background To solve the problem of an insufficient supply of dairy products in Tibet, work has been carried out to improve native dairy cattle and introduce purebred dairy cattle from low-altitude areas. The harsh environment of the plateau not only severely limits the production performance of high-yielding dairy cattle, such as Holstein and Jersey cattle, but also challenges their survival. The population structure and plateau adaptation mechanism of plateau dairy cattle are rarely reported. In this study, key genes and pathways affecting plateau purebred and crossbred dairy cattle were explored using genetic chip information. Results The results showed that the genetic diversity of the Tibet dairy cattle population was higher than that of the native cattle and plains dairy cattle. Purebred Holstein and Jersey cattle in Tibet were genetically closer to dairy cattle in the plains, and crossbred dairy cattle were admixed with more Tibet cattle and Apaijiza cattle. Based on the fixation index (FST), integrated haplotype score (iHS), and cross-population extend haplotype homozygosity (XP-EHH) approaches, 60 and 40 genes were identified in plateau Holstein and Jersey cattle, respectively. A total of 78 and 70 genes were identified in crossbred cattle compared to Holstein and Tibet cattle respectively. These genes are related to cardiac health and development, neuronal development and function, angiogenesis and hematopoietic, pigmentation, growth and development, and immune response. Conclusions Our results provide a glimpse into diverse selection signatures in plateau dairy cattle, which can be used to enhance our understanding of the genomic basis of plateau adaptation in dairy cattle. These results support further research on breeding strategies such as marker-assisted selection and gene editing in plateau dairy cattle populations.